Laparotomía de urgencia por peritonitis primaria en paciente pediátrico previamente sano: reporte de caso - Dos Santos Ramírez, Jéshua Wandherley (2025)
Most  patients  who  present  with  sudden-onset  peritonitis  have  some  secondary  cause  such  as  acute  appendicitis or intestinal perforation. Primary peritonitis is an extremely unusual pathology as a cause of  acute  abdomen,  accounting  for  less  than  1-2%.  In  pediatric  patients,  the  clinical  presentation  may  be  similar  to  that  of  secondary  peritonitis  and  require  surgical  intervention.  We  present  the  case  of  a  pediatric patient with primary peritonitis, with signs and symptoms similar to acute appendicitis, who underwent exploratory laparotomy, which was non-therapeutic, since no secondary cause of peritonitis was found. This case discusses the usefulness of open surgery in these patients or whether there are better alternatives for preoperative management, mainly in health centers with limited resources where there are no imaging studies or instruments available for laparoscopic surgery.